Music Sampling On A Keyboard Arranger For A Solo Organ Player Of Dangdut Music In Lumajang - Ilham Maulana, Muhammad (Repertoar, 2025)
This study aims to: (1) analyze the sampling production process on arranger keyboards for single organ players of dangdut music in Lumajang Regency and (2) analyze the application of sampling on arranger keyboards. This study uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that (1) the sampling production process consists of three main stages, namely pre-production (technical preparation and sound setting), production (recording, editing, mixing, and multisampling), and post-production (mastering and format conversion). These stages ensure optimal sound quality and provide flexibility for musicians in creating distinctive musical characters; (2) sampling is applied by converting the sampling results into a format recognized by the keyboard system, such as .WAV and .KMP. Sampling is applied through two methods: looping to produce style and sequencer for song play. With the features available on Korg Pa 600, musicians can apply sampling more easily and remix to harmonize with other instruments.